1990
DOI: 10.4141/cjas90-003
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH AND MATERNAL PERFORMANCE OF TWO-YEAR-OLD F1 AND RECIPROCAL BACKCROSS HEIFERS IN TWO ENVIRONMENTS

Abstract: Growth patterns and calf performance of 2-yr-old F1 and reciprocal backcross females were compared in two contrasting environments, semi-intensive management (Brandon, Man.) and extensive range management (Manyberries, Alta.). At Brandon, 621 heifers of Hereford × Angus (HA), Simmental × Shorthorn (SN), Charolais × Shorthorn (CN) and reciprocal backcrosses from Charolais × Hereford (CH), Charolais × Angus (CA), Charolais × Shorthorn (CN), Simmental × Hereford (SH), Simmental × Angus (SA), and Simmental × Short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 5 publications
3
8
0
Order By: Relevance
“…Manitoba, or under extensive .ung" rnu-nugement at Manyberries, Alberta, in the years [1981][1982][1983][1984][1985][1986]. Complete details of the development and management of the crossbred cow populations were documented by Rahnefeld et al (1990).…”
Section: Cattle Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manitoba, or under extensive .ung" rnu-nugement at Manyberries, Alberta, in the years [1981][1982][1983][1984][1985][1986]. Complete details of the development and management of the crossbred cow populations were documented by Rahnefeld et al (1990).…”
Section: Cattle Populationsmentioning
confidence: 99%
“…, the maternal performance of crossbred cows (Fredeen et al 1981(Fredeen et al ,1982a(Fredeen et al ,1982bMcKay et al 1990), the efficiency of crossbred cows (Fredeen et al 1987(Fredeen et al , 1988, and the carcass characteristics of crossbred calves (Rahnefeld et al 1983a(Rahnefeld et al ,b,c, 1984. The primary purpose of the research reported here was to compare the slaughter and carcass characteristics ofheifers and steers born to cows representing several European x British F1 and backcross genofypes and one all-British F1 cross (Hereford x Angus).…”
Section: Canadian Journal Of An'mal Sc'encementioning
confidence: 99%
“…Complete details of the development and management of the crossbred cow populations were documented by Rahnefeld et al (1990).…”
Section: Materials and Methods Cattle Populationsmentioning
confidence: 99%
“…Environmental and genetic effects on growth, including management differences, can influence the overall ranking of individuals when evaluated in relation to productivity (Fitzhugh et al 1967). Rahnefeld et al (1990) studied the growth and development of first-cross (F1) and reciprocal backcross females under extensive range and semi-intensive farm conditions.…”
mentioning
confidence: 99%
“…This study, from phase IV of the Foreign Cattle Breed Evaluation (Rahnefeld et al Rahnefeld et al (1990).…”
mentioning
confidence: 99%